Dynamicizing the Discourse of Hadith: Study of HR. Bukhārī No. 1291 and Abū Dāwūd No. 4291 from a Philosophical Hermeneutics Perspective - Fachruli Isra Rukmana; Aldi Hidayat; Nur Laili Nabilah Nazahah Najiyah; Mohammad Fahmi Abdul Hamid; Sri Kurniati Yuzar (An-Nida')
The study of ḥadīth has experienced stagnation compared to the study of the Qur'an, which tends to show a proliferation of ideas. The dominance of isnād (chain of transmission) studies, debates over the designation of ḥadīth as a secondary source of Islam, and the use of certain ḥadīth to reject renewal have played central roles in the stagnation of ḥadīth. One ḥadīth often used to oppose renewal is the prohibition against lying in the name of Muhammad, as narrated by al-Bukhārī. This ḥadīth will be reexamined through the lens of the ḥadīth on tajdīd (renewal). However, before proceeding to this reading, this article proposes three research questions correlating with the stagnation of ḥadīth discourse. First, how has the discourse of ḥadīth developed in the modern world? Second, how can Gadamer’s hermeneutics, as an ontological framework, be applied to revitalize ḥadīth discourse? This research is qualitative in nature, employing a library research approach. It produces two conclusions. First, (elaborate on the stagnation of ḥadīth alongside the shortcomings of modern interpretations). Second, classical and modern ḥadīth sciences have yet to fully guarantee the authenticity of matn (content) exactly as intended by the Prophet, even though the prohibition against fabricating ḥadīth implicitly demands the sterilization of ḥadīth from additional phrasing by narrators. Therefore, this article proposes originalization as the implicit call of the ḥadīth narrated by al-Bukhārī, as well as the practice of the ḥadīth on tajdīd narrated by Abū Dāwūd. Originalization will eventually open new avenues for ḥadīth discourse, such as ḥadīth revisionism, memory phenomenology, the archaeology and anthropology of narrators, and more.